(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, we will analyze the Father’s Gate, which is located in the western part of the city of Khiva and is currently decorated with symbolic symbols and inscriptions. There are four gates in Khiva, today the main entrance is Ota Gate.